Characterisation of a novel sustainable wood-geopolymer masonry units - Firesenay Zerabruk Gigar; Amar Khennane; Jong-Leng Liow; Biruk Hailu Tekle; Zongjun Li (Developments in the Built Environment)
Masonry units have been fundamental to building construction for over 6000 years, making them one of the oldest and most widely used materials in the industry. However, their production using ordinary Portland cement has significant environmental impacts, including high carbon dioxide emissions and depletion of natural resources. This highlights the need for more sustainable alternatives. One promising option is the use of recycled aggregates from construction and demolition waste in masonry unit manufacturing. This paper investigates the use of chipped waste timber as aggregates, bound together with geopolymer cement made from industrial by-products such as fly ash and slag. The result is a new type of masonry units, referred to as wood geopolymer masonry units (WGMUs), which were evaluated against established standards and compared with conventional masonry units (CMUs). The innovative WGMUs demonstrated improved ductility and reduced density compared to CMUs, making them easier to handle and lighter in construction. They also have a distinctive, rustic texture and consistent dimensions that meet Australian standards. Although WGMUs exhibited higher water absorption and drying contraction due to their wood content, these characteristics generally remain within acceptable limits, supporting their potential as eco-friendly construction materials.